5G technology and smart agriculture to aid Indian farmers - Gakhar, Shalini; Sharma, Sheetal; Sahoo, Rabi (CGIAR System Organization, 2024)
Since October 2022, India has embarked on the fastest rollout of 5G mobile data in the world, with average download speeds nearing 100 megabits per second. Agriculture is one of the fields set to be impacted: here we share five ways in which 5G can enable more productive smart farms in India.